When Family Policy Doesn’t Work: Motives and Welfare Attitudes Among Childfree Persons in Poland - Szelewa, Dorota (2022)
The primary goal of this article was to analyse the welfare attitudes of people self‐declaring as childless by choice alongside the exploration of their social experience as childfree persons in the context of a rapid increase in the generosity of pro‐natalist public policies in Poland. The analysis is based on semi‐structured interviews conducted with 19 respondents recruited via Facebook network groups. Thematic analysis was applied identifying six general themes: “satisfied and never had the need”; “dealing with social pressure”; “family measures—yes, but not this way”; “unfair treatment of the childfree”; “towards welfare state for all”; and “change my mind? Never, even if offered one million dollars.” The research demonstrated that childfree persons present favourable views on state support for families with children. While critical of cash‐based family support, respondents have a clear preference for investing in services enabling women to participate in the labour market. Finally, if public policies aimed at removing barriers to parenthood were strengthened, this would not change the respondents’ minds about procreation.